Understanding teacher agency in implementing inclusive education policy: a mixed-methods study of private schools under India’s right to education act - Tripathi, Tarang (Frontiers in Education, 2025)
Teacher agency has emerged as a critical factor in educational reform, yet research remains heavily concentrated in Western contexts with limited attention to how demographic and contextual factors shape teachers’ capacity to serve diverse student populations. This study addresses this gap by examining teacher agency in Indian private schools implementing Section 12(1)(c) of the Right to Education Act, which has brought over 22 million economically disadvantaged students into private schools. Using a concurrent embedded mixed-methods design, 125 teachers were surveyed across two private schools in Delhi, India. The study employed an adapted 21-item teacher agency scale alongside open-ended questions, applying an ecological framework that examines agency across individual, micro, meso, and macro levels. Quantitative analyses included regression modeling to identify predictors of agency, while qualitative responses underwent thematic analysis to understand factors supporting and constraining teachers’ experiences. Demographic characteristics showed limited influence on teacher agency, challenging assumptions about individual qualifications determining effectiveness in diverse classrooms. Principal and staff support emerged as the strongest predictor of agency outcomes. Qualitative findings revealed the complex, multilayered nature of teacher agency, with factors spanning individual, micro, meso, and macro ecological levels. Principal leadership support and peer collaboration emerged as critical institutional enablers of agency, while parent interactions functioned as both constraints and supports depending on relational dynamics. Teacher beliefs about student capabilities and family engagement significantly shaped their sense of professional agency. The findings demonstrate that teacher agency emerges through complex interactions across ecological levels rather than from individual attributes alone. These findings challenge recruitment-focused policy approaches by demonstrating that contextual factors matter more than individual characteristics in shaping teacher agency. The results suggest that sustainable inclusive practices require institutional-level interventions rather than individual-focused solutions, with implications extending beyond the Indian context to global discussions of teacher agency in diverse educational settings.